"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle

N'est pas mère qui veut. Le paradoxe de l'adoption internationale - Reysoo, Fenneke; Bos, Pien (Nouvelles Questions Féministes, 2011)
La circulation d’enfants entre une mère biologique et des parents adoptifs soulève des questions sur la pluralité des systèmes de genre et les inégalités sociales méconnues jusqu’ici. Nous menons une réflexion sur la situation paradoxale qui lie deux systèmes de genre : en Inde, il enjoint des femmes non mariées à renoncer à vivre leur maternité et, en Occident, il pousse les femmes avec un emploi à retarder la conception de leur premier enfant, ce qui augmente le risque de fécondabilité réduite et ouvre la voie au recours à l’adoption. Notre étude, au Tamil Nadu (Inde), parmi les mères biologiques montre que la production d’enfants adoptables relève de rapports de pouvoir très complexes.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; asie; corps; cours; discipline; inde; justice reproductive; justice sociale; maternité; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; sexualité; soc3113; sociologie; systèmes d'oppressions; thématiques

A new Vision for advancing our movement for reproductive health, reproductive rights and reproductive justice - Asian Communities for Reproductive Justice (Asian Communities for Reproductive Justice, 2005)
Forward Together’s (then Asian Communities for Reproductive Justice or ACRJ) groundbreaking analysis of the framework and vision for reproductive justice, described by organizations and funders as revelatory and pivotal to the field.
Keywords: amériques; approches et analyses; asie; droits des femmes*; femmes* asiatiques; femmes* de couleur; inégalités; justice reproductive; justice sociale; militance; racisme; ressource en ligne; régions géographiques; santé; santé reproductive; sexisme; sexualité; systèmes d'oppressions; thématiques; éducation sexuelle; états-unis